Designing an Arduino-based Automatic Cocoa Fermentation Tool - Balkhaya, Balkhaya; Ilham, Dirja Nur; Candra, Rudi Arif; Hasbaini, Hasbaini; Anugreni, Fera (Politeknik Ganesha Medan, 2020)
Automatic cocoa fermentation design is expected to facilitate the work of cocoa farmers during the process of reversing and stirring cocoa fermentation based on the right temperature. The fermentation process is of course done in a box or sack so that chocolate quickly produces heat and is cemented. However, in certain conditions, especially when in sacks there are often obstacles in the stirring process. Often the fermented chocolate experiences weathering or moldiness due to the uneven reversal that causes chocolate to clot, causing weathering or moldiness and produce an unpleasant odor and unattractive color on the cocoa beans. To overcome this problem a tool that automatically can turn or stir the cocoa beans evenly. This device is controlled by Arduino Uno R3 with a sensor that is an LM35 temperature sensor and has an LCD output and DC motor. This tool uses Relay to adjust the delay when driving a DC motor. The working principle of this tool, when the LM35 temperature sensor receives heat conditions on the cocoa beans, the LCD will display the condition of the temperature while the relay will instruct the DC motor to move the Cocoa Fermentation rail rotating left or right. The purpose of making this tool is to create a tool that can help alleviate the work of cocoa farmers in cocoa bean stirring activities at the time of cocoa bean fermentation controlled by Arduino. From the results of the tests carried out, the tool is able to read both hot and cold temperature conditions, and the LM35 sensor can work well in detecting temperature changes from 350C to 400C or vice versa.